NEW DRUG DELIVERY SYSTEM OF DOUBLE MATRIX CAPSULE CONTAINING LACTOBACILLUS BACTERIA IN THE BIOSCIENCE - Dae-Seop Kim, Mi-Ey Park, So-Yeun Yoo, and In-Young Kim (International Journal of Research Science and Management, 2014)
This study is to develop the double matrix capsulation biotechnology in order to increase the conservativeness and stability of lactobacillus bacteria, to be deliciously flavored and give it visually differential effect in healthy food industries, were described. In order to eat easy for wellbeing life science, as the first capsulation with o/w (oil-in-water) emulsifying system, our study group was especially made to soft and moisture cream using 5wt% of sucrose ester emulsifier as the first capsule containing lactobacillus bacteria. Nutrient agents were used with botanical squalane, camellia japonica seed oil. Double matrix capsulation was formed with the best stabilized bead type capsules when it blended 1 : 3 ratio of chitosan and sodium alginate. The bead diameter size was about 2.0~5.0mm (mean diameter: 3.8mm). Activity of lactobacillus bacteria containing sweet cream for depending on various pH variations showed that alkalinity (pH=10.80.8) condition was higher than acidity (pH=4.20.3) and neutrality (pH=7130.2) conditions. After a month, it also was certified to the activity of lactobacillus bacteria in incubated at 373˚C in culture medium. As application of food industry, we developed the containing lactobacillus bacteria capsule and 4 colored kinds of double matrix capsulation in commercial yogurt cream. As for above mentioned those of results, one of tool to stabilize the living lactobacillus bacteria, doubled matrix capsulation greatly be expected to contribute to food industry. Furthermore, it can be expected to apply the drug delivery system (DDS) having good healthy food with active ingredients of stabilizing technologies at drugs, pharmaceutical divisions and skin care cosmetic industry..